NUMERICAL EVALUATION OF UNSATURATED FLOW IN POROUS MEDIA USING ITERATIVE TECHNIQUES FOR VARIOUS SOILS (Malaysian Journal of Civil Engineering, 2018)
Unrelenting difficulties that arise in forming numerical solutions of water flow in variably saturated problems include controlling the stability of the nonlinear equation solver. Besides, the accuracy of solutions, also of concern is the required computational effort, especially when nonlinear soil hydraulic properties and dry initial conditions are involved. A general numerical algorithm in the context of finite element formulation and Picard and Newton iteration schemes are described to solve Richards’ equation, in which a mass-conservative, head based formulation is proposed to approximate the governing equation, and mass-lumping techniques is employed to improve solution convergence and stability behavior. A difficult one-dimensional test case presented emphasizes different aspects of the performance of the iterative methods and the different issues that can influence their convergence and efficiency. The result is validated with extensive average values of soil hydraulic parameters for 12 soil textural groups.